دور المظاهر الإستراتيجية لتقويم أداء الموارد البشرية في تحسين إنتاجية العمل دراسة تطبيقية في معمل سمنت الكوفة - أزهار نعمة أبو غنيم (مجلة الغري للعلوم الاقتصادية والادارية)
المستلخص: یهدف البحث إلى د ا رسة وقیاس المظاهر الإست ا رتیجیة لتقویم أداء الموارد البشریة (الإلت ا زم، القیادة، الثقافة، المرونة، التعلم، والتمكن) في المجتمع المدروس (معمل السمنت / كوفة) ومن ثم تحلیل وتقصي أثر هذه المظاهر على إنتاجیة العمل وما یؤثر علیها من عوامل (القدرة على العمل، الرغبة في العمل، وبیئة العمل) وتقدیم التوصیات المناسبة التي من شأنها تمكین المعمل المبحوث من التعرف على المظاهر الإست ا رتیجیة لتقویم أداء الموارد البشریة و مدى تأثیرها في إنتاجیة العمل، والعمل على تطویرها لما لها من تأثیر في سلوك الأف ا رد العاملین ، وفي نجاح المعمل و قدرته على الاستم ا رر والتطور، وٕایضاحا لما تقدم تم بناء أنموذج افت ا رضي یحدد العلاقة بین المتغیر المستقل (المظاهر الإست ا رتیجیة لتقویم أداء الموارد البشریة) والمتغیر المعتمد (إنتاجیة العمل) نتجت عنه فرضیة رئیسیة انبثقت منها مجموعة من الفرضیات الفرعیة تظهر العلاقة والتأثیر، وقد تم اختیار عینة من العاملین في معمل السمنت/كوفة قسم التعبئة، وقد تم التوصل الى مجموعة من الاستنتاجات لإج ا رء البحث واختبار فرضیاته، ولجمع البیانات عن متغی ا رت البحث اعتمدت استمارة استقصاء بهدف تدعیم دقة بیانات الاستمارة وتحلیل النتائج واستخرجت النتائج باستخدام الحاسوب . Role of Strategic appearances for evaluating the performance of human resources in improving the productivity of labor An Empirical Study in Kufa Cement Factory Abstract The research aims to study and measure aspects of the strategy for evaluating the performance of human resources (commitment, leadership, culture, flexibility, learning, and mastery) in the community studied (Lab cement / Kufa) and then analyze and investigate the impact of these appearances on the productivity of labor and what affects it of factors (the ability to work, willingness to work, and the work environment) and make appropriate recommendations that would enable the respondent from the lab to identify the manifestations strategy for evaluating the performance of human resources and its impact on labor productivity And working to develop because of their effect on the behavior of individual employees, and the success of the lab and its ability to continue and development, and an explanation of what progress has been building model by default defines the relationship between the independent variable (manifestations strategy for evaluating the performance of human resources) and the dependent variable (labor productivity) resulted in major premise emerged, including a set of hypotheses sub show the relationship and influence, has been selected sample of workers in the plant cement Kufa packing department, has been to reach a set of conclusions to conduct research and test hypotheses, and to collect data for research variables adopted a questionnaire in order to strengthen the accuracy of the data format and the analysis of the results and the results were extracted using the computer.